Giacomo Beltrami : the "Accidental Tourist" in Minnesota - Bell, Robert (My University, 2012)
The purpose of this study was to identify the American Indian artifacts that Giacomo Beltrami collected while travelling in Minnesota to find the Mississippi River's source during 1823.
Color poster with text and maps.
Keywords: Beltrami, Giacomo Costantino, 1779-1855; Mississippi River Valley--Description and travel; Indians of North America--Mississippi River Valley; Posters